Nevoid basal cell carcinoma syndrome: a review of the literature and a report of a case - G. BAKAEEN, L. D. RAJAB, F. A. SAWAIR, M. A. M. HAMDAN, & N. D. DALLAL (Paediatric Dentistry, 2004)
The purpose of this paper is to report the development of multiple odontogenic keratocysts (OKCs) in a 15-year-old female with nevoid basal cell carcinoma syndrome (NBCCS) and review the literature pertinent to NBCCS. Although more than 100 abnormalities have been reported in NBCCS, the development of OKCs is one of its principle features. In view of this, the patient was subjected to further medical, dermatological and radiographic investigation. Multiple basal cell naevi and skeletal anomalies associated with NBCCS were found. Because of the autosomal dominant inheritance of this syndrome, the patient’s family was then investigated.